Comparative study on usefulness of modified WHO Partograph in management of labour at one of the rural teaching institutes of Gujarat, India - Ninama, Shilpa N.; Gandhi, Mayur R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Modified WHO Partograph is a simple, inexpensive pre-printed form on which labour observation are recorded. It generally comprises three sections of information: maternal condition, fetal condition and labor progress. To study on usefulness of Modified WHO Partograph in management of labour of low risk women, this indirectly improved maternal and perinatal outcome. Methods: In this study the progress of labour of 150 women with uncomplicated full term pregnancies with cephalic presentation in active labour was studied using modified WHO partograph. 150 historical matched controls comprising of low risk women who delivered without the use of partograph were identified from the labour register and their course of labour studied. The hospital records were studied to obtain the demographic variables. Maternal and perinatal outcome was analyzed for both cases and controls. Results: The emergency cesarean section rate was reduced from 38.7% in controls to 24.7% in cases and both are significant statistically. None of the cases had labour beyond 16 hours, thus indicating significant reduction in prolonged labour. Neonatal intensive care admissions decreased from 18.6% in controls to 6% in cases indicating an improved maternal and neonatal outcome. Conclusions: Modified WHO Partograph work as “early alarming warning system” which help in detecting delayed progress of labour which improves maternal as well as perinatal outcome.